THE ROLE OF FRANCE AS A CO-CHAIR OF THE MINSK GROUP (OSCE) DURING THE SECOND KARABAKH WAR - Kazimova , Zeynab (Collection of scientific papers «ΛΌГOΣ», 2022)
The Nagorno-Karabakh conflict is the longest conflict in the post-Soviet space. In 1988, ethnic Armenians living in Nagorno-Karabakh illegally demanded the transfer of the territory of the Nagorno-Karabakh Autonomous Region (NKAO) from Azerbaijan to Armenia.